The Economic Journalists Association of the Philippines (EJAP) and its role in promoting professional development of member reporters - Cuevas, Likha Castillo; Khan, Rachel E. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2010)
This thesis examines how the Economic Journalists Association of the Philippines (EJAP) contributes to the professional development of its members by assessing its activities (Training, Sportsfest, Awards, and Christmas Party) using the definition of professionalism as provided by the organization's board of directors nd by literature; and 2) through the perceptionof itsmembersand newspaper editors.It used System theory as a tool in examinin the organization; employed Normative theory in seeking the definition of professionalism in the context of what is ideal and hw EJAP board members saw it; and applied Social Construction theory when it relied on how business reporters see themselves in the context of their work. Based on literature and interviews with EJAP board members, professionalism can be defined through four major categories: 1) serving public interest; 2)media gatekeeping; 3) good interpersonal relationships; and 4)ethics. Survey results also showed that respondents strongly agreed that the Training and Awards contribute to their professional development and they just agreed that the Sportsfest and Christmas Party also contribute in that aspect. Based on the Professionalism Index - wherein an activity could havea maximum possible rating of 88.9 percent- respondents said that these activities contribute to their professional development as shown by the ratings that ranged from 73 percent to almost 82 percent. Generally, the editors said the EJAP activities and EJAP as an organization, perceived through these activities, help in the professional development of its members. Except for the Business World editor, all of them said EJAP or some of its activities could help fill in the gaps that are needed by reporters. Through the theories utilized by this study, EJAP was scrutinized by investigating how the organization worked vis a vis its members, i.e. through input-output mechanism; what the organization's input should be or how it should be executed; and the results of these inputs based on the realities that the members faced in the performance of their duties as journalists. In this respect, future studies could be done to include other elements outside the system or organization, investigating EJAP through organizational culture, or using learning theories in evaluating the organization's activities.
Thesis (M.A. Media Studies - Journalism)--University of the Philippines Diliman
Keywords: Journalists